The Parents Experience in Caring Children with Learning Difficulties in Children and Adolescent Polyclinic in National Mental Health Hospital - Windy Freska; Zabidah Putit; Reni Dayati (Faculty of Nursing, Universitas Andalas, 2018)
Purpose: This exploratory, qualitative study was conducted to explore parents experience for parenting a child with learning difficulties . Method: We recruited a purposive sample of 6 mother who were caring for a child with learning difficulties at home from children and adolescent Polyclinic in national Mental Health Hospital, semi-structured interviews between April and June 2015. Each interview lasted for about an hour. We analyzed the interview data using qualitative content analysis. Data was analyzed by applying Collaizi technique. Findings: The research identified themes: Provide an emotional response and physical response in parenting, Participants face challenges in accepting and adapting to their child's learning difficulties in the form of emotional responses as well as physical responses. Conclusions: Our findings indicate a few important educational needs of parents in caring for a child with learning difficulties To facilitate effective parenting, holistic and individualized needs assessment, families especially mothers will face challenges in accepting and adapting to their children such as stress, changes in the lifestyle of the mother and her family, In addition to adapting to the condition of the child, the mother also struggles to be able to face the pressure in treatment and confusion in the future for her child.